Tiger, Tiger : [his life, as it's never been told before] - Patterson, James, 1947- (Little, Brown and Company, 2024)
"On April 13, 1986, ten-year-old Tiger Woods watches his idol, Jack Nicklaus, win his record sixth Masters. Just over a decade later, chants of "Ti-ger, Ti-ger!" ring out as the twenty- one-year-old wins his first Green Jacket. He blazes an incredible path, winning fourteen major titles (second only to Nicklaus himself) by the time he's thirty- three, smashing records and raising standards. Then come multiple public scandals and potentially career-ending injuries. The once-assured champion becomes an all-American underdog. "YouTube golfer" is how his two children know their father--winless since 2013--until he wins the 2019 Masters, his fifteenth major, before their eyes. But the story doesn't end there. Tiger, Tiger is the first full-scale Woods biography of the decade. In James Patterson's hands, this story is a hole-in- one thriller."--Amazon.